Crowdinvesting in entrepreneurial projects: disentangling patterns of investor behavior - Maximilian Goethner; Sebastian Luettig; Tobias Regner (Small Business Economics, 2020)
Crowdinvesting emerged recently as an alternative way of funding for start-up projects. Our dataset consists of 16,666 investments made at Companisto, one of the largest crowdinvesting platforms in Europe. Using cluster analysis based on individual investment decisions, we find that crowdinvestors differ in their investment strategies and motivations. We can distinguish three types of crowdinvestors: Casual Investors, Crowd Enthusiasts, and Sophisticated Investors. The types also vary in their response to project quality signals, project-related information reducing the degree of uncertainty, and social influence by fellow investors. We conclude that crowdinvestors are anything but a homogeneous group. Instead, they are motivated by different factors and respond to different signals when making investment decisions.
Keywords: G23; G41; L26; 330; Crowdinvesting; Entrepreneurial finance; New ventures; Cluster analysis; Social influence; Signaling